Ultra high performance liquid chromatography technique to determine imidacloprid residue in rice using QuEChERS method - Chokeli, Raihanah; Hashim, Zailina; Ho, Yu Bin; Mohd Elias, Saliza; Mazlan, Norida (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Imidacloprid residue analysis in paddy samples was conducted using the simplified and validated QuEChERS preparation method. Samples were extracted with acetonitrile (ACN) and salts anhydrous magnesium sulphate (MgSO4) and sodium chloride (NaCI) while cleaning was by treating with primary secondary amine (PSA). Imidacloprid residue was quantified with Ultra High Performance Liquid Chromatography (UHPLC) using short and narrow C18 column to reduce analysis duration and solvent consumption. The pumps were programmed to mix acetonitrile and water at a ratio of 2:8 to form the mobile phase, with a flow rate of 0.1 mL/min and10 μl injection volumes. Imidacloprid was detected at 270 nm using UV detector. The method was validated in term of linearity, range, limit of detection (LOD), limit of quantification (LOQ), precision (repeatability and intermediate precision), and accuracy (recovery). The LOD was 0.001 mg/L whereas LOQ was 0.003 mg/L. The validated method provides good analytical results wherein the linearity r2 was 0.9996, recoveries 80−120% and RSDs <20%. This method can be implemented in routine laboratories as it yields a higher sample throughput and reduced solvent consumption compared to the traditional Luke method approach.